2020
DOI: 10.1007/s10865-020-00188-5
|View full text |Cite
|
Sign up to set email alerts
|

Treating postpartum depression in rural veterans using internet delivered CBT: program evaluation of MomMoodBooster

Abstract: We especially thank Danaher and Tyler for their work in adapting the program to fit the requirements of our VA trial and for providing support/training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…The MMB library also includes articles on relaxation, problem solving, and getting support for parenting (for further details on the development of the program, see the study by Danaher et al [ 41 ]). As described in earlier publications [ 42 , 43 , 60 , 61 ], to encourage optimal engagement and resulting behavior change [ 57 ], although the intervention can be accessed and used on smartphones, MMB was designed and optimized for use on desktop computers, laptops, and tablets and designed to function on popular browsers for both Windows PCs and Mac computers.…”
Section: Methodsmentioning
confidence: 99%
“…The MMB library also includes articles on relaxation, problem solving, and getting support for parenting (for further details on the development of the program, see the study by Danaher et al [ 41 ]). As described in earlier publications [ 42 , 43 , 60 , 61 ], to encourage optimal engagement and resulting behavior change [ 57 ], although the intervention can be accessed and used on smartphones, MMB was designed and optimized for use on desktop computers, laptops, and tablets and designed to function on popular browsers for both Windows PCs and Mac computers.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it can be inferred that internet CBT helps mothers in the intervention group feel less depressed than mothers in the control group. 14 There is currently an innovative increase in internet-based interventions. According to a study related to internet-based treatment, they found that patients who can attend treatment responsibly can benefit more from Internet-based treatment.…”
Section: Discussmentioning
confidence: 99%
“…The program from which these data were collected consisted of 6 self-directed, postpartum-specific, web-based CBT–based modules and 6 weekly concurrent phone coaching calls. A previous study described quantitative metrics of engagement and outcomes and provided further information regarding the methods of the intervention study [ 35 ]. On average, veterans engaged in 3.35 coaching calls and spent an average of 49.19 minutes on the phone with their coach over the course of their engagement with the program.…”
Section: Introductionmentioning
confidence: 99%
“…On average, veterans engaged in 3.35 coaching calls and spent an average of 49.19 minutes on the phone with their coach over the course of their engagement with the program. Effect sizes for depressive symptoms, behavioral activation, and automatic thoughts were large [ 35 ]. Because alliance effects for IPIs have been attributed to participant relationships with the IPI programs in some studies [ 19 , 28 ], this analysis quantifies the frequency of responses related to each for comparison.…”
Section: Introductionmentioning
confidence: 99%